Robotic lateral oropharyngectomy following diagnostic tonsillectomy is oncologically safe in patients with human papillomavirus‐related squamous cell cancer: Long‐term results. Issue 12 (3rd September 2022) - Siddiq, Somiah; Stephen, Sarah; Lin, Daniel; Fox, Hannah; Robinson, Max; Paleri, Vinidh
Abstract: Introduction: To report the long‐term oncological and functional outcomes of en bloc TORS lateral oropharyngectomy to address the close/involved margin following diagnostic tonsillectomy in HPV‐related SCC of unknown primary. Material and methods: A single tertiary center observational cohort over a 4‐year period. Primary outcome measures were disease‐specific survival (DSS), overall survival (OS), and PSS NOD (Performance Status Scale‐Normalcy of Diet) scores. Results: TORS specimens did not evidence residual carcinoma in 93% of patients. Of 14 patients, 50% received surgery alone (median follow‐up 57 months; range 46–96), the remainder surgery and adjuvant therapy (median follow‐up of 58 months; range 51–69) with 100% DSS, OS and no deterioration of PSS NOD scores. Conclusions: Long‐term oncological outcomes confirm TORS lateral oropharyngectomy alone is an oncologically safe treatment. Due consideration of this approach is warranted to mitigate against the morbidity of adjuvant radiotherapy treatment in this group of patients.